THE ORIGIN OF LETTUCE AND METHODS OF GROWING IT ON A GLOBAL SCALE (BASED ON HYDROPONICS). - Kuchkorova Gulasal (TADQIQOTLAR, 2025)
Abstract Lettuce (Lactuca sativa L.) is a globally recognized leafy vegetable known for its nutritional value and versatility. The cultivation of lettuce in hydroponic systems, specifically using the Nutrient Film Technique (NFT) and Deep Flow Technique (DFT), has gained popularity for its efficiency and environmental sustainability. This study explores the effects of biofertilizers, including Plant Growth-Promoting Rhizobacteria (PGPR), Arbuscular Mycorrhizal Fungi (AMF), and microalgae, on the growth performance of lettuce in hydroponic systems. Lettuce plants were grown under controlled environmental conditions, with consistent nutrient solution management, including pH and electrical conductivity adjustments. Biofertilizers were applied at different concentrations (50% MF + B, 50% MF + AMF, 50% MF + microalgae) to assess their influence on growth parameters such as leaf area, leaf number, plant height, and biomass. The results revealed that biofertilizers significantly improved lettuce growth, with PGPR treatment yielding the greatest increase in leaf area and biomass. These biofertilizers contributed to enhanced nutrient availability and improved root health, promoting better growth compared to control groups. The findings highlight the potential of biofertilizers to optimize hydroponic lettuce production by improving resource use efficiency and fostering sustainable agricultural practices. This study offers valuable insights into hydroponic lettuce cultivation and the integration of biofertilizers as a promising solution for improving plant growth and yield in controlled environments.